Platelet-Rich Fibrin Enhances Fracture Healing in Tibial Long Bone: An Experiment in Rabbit - Nucki Nursjamsi Hidajat; Dicky Mulyadi; M. Rizal Chaidir; Taufan Herwindo Dewangga (Althea Medical Journal, 2020)
Background: Fracture on long bone is a complicated case to manage. Bone graft procedure involving growth factors has been widely studied with promising results. Recently, platelet-rich fibrin (PRF) has been introduced as having potential in healing process. This study aimed to explore the quality of fracture healing on long bones treated with bone graft with and without PRF combination.Methods: This study was conducted between October to November 2018 on 18 rabbits that were divided into 2 groups. A 5 mm fracture was created on tibial bones and the fracture was stabilized using a 2.0 mm mini plate. The defect was then treated by an autogenic bone graft with and without  PRF. Histological analysis was conducted 3 weeks after the treatment and a scoring was performed using the Salkeld system. The quality of union; cortex development and remodeling; and bone graft incorporation and new bone formation were then analyzed.Results: There were significant differences between fractures in rabbits given PRF than those without PRF in terms of  union quality (p 0.040), cortex growth and remodeling (p 0.0001), bone graft and new bone union (p 0.0001), as well as in the total Salkeld score (p 0.0001).Conclusion: PRF given with bone graft therapy can enhance the quality of fracture healing of a long bone. Further studies on how the PRF content influences fracture healing process needs to be performed to further explore this effect.